Association between serum transthyretin and intracranial atherosclerosis in patients with acute ischemic stroke - He, Jinfeng; Zhu, Jiamin; Zhang, Wenyuan; Zhan, Zhenxiang; Fu, Fangwang; Bao, Qiongqiong (Frontiers in Neurology, 2022)
Background: Intracranial atherosclerotic stenosis (ICAS) is the primary cause of ischemic stroke. In addition to dyslipidemia, inflammation has been recognized to be potential pathogenesis in the process of atherosclerosis. As an inflammatory index, it is still unknown whether there is a link between transthyretin and ICAS. Methods: Consecutive patients with acute ischemic stroke admitted to the Second Affiliated Hospital of Wenzhou Medical University from January 2019 to June 2020 were retrospectively analysed. Blood samples were taken from all patients within 24 hours after admission to detect serum transthyretin levels. ICAS was defined as the detection of at least one intracranial artery stenosis on vascular examination, with the degree of stenosis ≥50%. Multivariable logistic regression analysis was used to identify independent factors associated with ICAS. Restricted cubic spline models were further used to depict the patterns in the association between serum transthyretin levels and ICAS. Results: A total of 637 patients with acute ischemic stroke were included in the study, of whom 267 (41.9%) suffered from ICAS. Compared with the patients without ICAS, serum transthyretin levels in patients with ICAS were significantly lower (226.3 ± 56.5 vs 251.0 ± 54.9 mg/L, p<0.001). After adjusting potential confounders, patients in the lowest tertile showed a significant increase in ICAS compare to those in the highest tertile (OR, 1.85; 95% CI, 1.12-3.05; p =0.016). This negative linear association was also observed in the restricted cubic spline model. Age, NIHSS score, HbA1c and low-density lipoprotein cholesterol were also independently associated with ICAS. Conclusions: Decreased serum transthyretin levels are associated with more severe burden of ICAS in patients with acute ischemic stroke. Our findings suggest that transthyretin may play a role in the pathogenesis of ICAS and provide the insights in further clinical researches to control inflammation for the treatment of ICAS.